Pengaruh Pelatihan Dan Pengembangan Karir Terhadap Kinerja Karyawan Pada The Springs Club Gading Serpong Kab Tangerang - Aditya Indrajaya Rusmana; Maghfiroh Yanuarti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The purpose of this study is to determine the Effect of Training and Career Development on Employee Performance at The Springs Club Gading Serpong both partially and simultaneously. The research method used in this study is quantitative. The sampling technique in this study is Probability Sampling with a sample of 62 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, determination coefficients and hypothesis tests. The results of the study indicate that there is a positive and significant influence between training on employee performance. Where the simple linear regression equation Y = 12.544 + 0.644 X1. The correlation value is 0.639. The coefficient of determination value is 40.9%. The calculated t value> t table or (6.442> 1.670) with a significance of 0.000 <0.05. Career Development has a positive and significant effect on employee performance. This can be proven from the simple linear regression equation Y = 14.422 + 0.094 X2. The correlation value is 0.697. The coefficient of determination is 48.5%. The calculated t value > t table or (7.523 > 1.670) with a significance of 0.000 < 0.05. Simultaneously, training and career development have a positive and significant effect on employee performance at The Springs Club Gading Serpong. This can be proven from the multiple linear regression equation Y = 4.764 + 0.424 X1 + 0.456 X2. The correlation value is 0.795. The coefficient of determination is 63.1%. The calculated F value > F table or (50.546 > 3.15) with a significance level of 0.000 < 0.05.